Organizational Identification as a Mediator of Organizational Support, Employee Engagement, and Commitment: The Case of Non-Teaching Employees in the Mindanao State University-Iligan Institute of Technology (MSU-IIT) - Mark Ronie O. DUROG; Pamela F. RESURRECCION (Journal of Human Resource Management)
Purpose – The primary objective of this study is to assess and compare the levels of organizational identification, employee engagement, organizational commitment, and perceptions of organizational support between contract-of-service and regular non-teaching employees in a state university in Iligan City. Aims(s) – This study investigates whether OI among contract-of-service and regular non-teaching employees mediates the relationships between OS, EE, and OC. Design/methodology/approach – This study used a cross-sectional quantitative research design. The respondents comprised 81 contract-of-service and 91 regular non-teaching employees from different offices in MSU-IIT using an online survey form. The collected data was analyzed using SmartPLS4 and Partial Least Square of Structural Equation Modeling (PLS-SEM) to test the hypotheses. Findings – The findings show that Organizational Identification (OI) significantly mediates the relationship between Organizational Support and Affective Commitment (AC), with stronger effects for contract-of-service employees. For contract-of-service and regular employees, OI is crucial in linking support and commitment. Regular non-teaching employees show stronger OI than temporary workers, enhancing their engagement and commitment. Limitations of the study and practical implications – Future research can also be conducted on a larger sample size, including other government higher educational institutions in Mindanao, to generalize the findings. One such limitation is the scope of this study, which is limited to a state university in Iligan City only. This work is limited to the MSU-IIT non-teaching employees; a cross-cultural study may be conducted to see if any variations occur in other cultural settings. A comparative study among the non-teaching employees of government and private higher educational institutions is also suggested. Originality - This research contributes to the broader understanding of employee dynamics, especially the non-teaching employees within the academic sector, specifically in the Philippine context, with implications for improving institutional performance and employee well-being.